The Right to Privacy: Tinjauan terhadap Penyalahgunaan Data Pribadi dalam Perspektif HAM - Saputra, Wahyudi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2023)
The privacy movement was created by Warren and Brandhuis, who wrote an article in Harvard Law School Journal title